Art Education in the Digital Era: Learning Strategies for the Digital Native Generation - Putut Ary Nurmansayah; Zakaria Surya Soeteja; Tri Karyono (Universitas Muhammadiyah Mataram, 2025)
Abstract: The digital transformation has significantly reshaped art education, particularly in adapting teaching approaches to suit the traits of digital native learners who are immersed in technology, visuals, and interactivity. This study is a Qualitative Research employing a literature analysis method to identify adaptive digital-based art learning strategies. Data were gathered from books, journal articles, and relevant online publications using targeted keywords. Thematic content analysis was applied to identify recurring patterns and issues, including blended learning models, STEAM integration, the digital divide, and teacher readiness. The findings indicate that integrating technology into art education not only enriches the creative process but also fosters critical thinking and innovation. As a result, art education curricula must strike a balance between traditional manual skills and contemporary digital approaches to establish an inclusive, progressive, and globally relevant education system.Abstrak: Transformasi digital telah mendorong perubahan signifikan dalam pembelajaran seni rupa, terutama dalam menyesuaikan pendekatan dengan karakteristik generasi digital native yang terbiasa dengan teknologi, visual, dan interaktivitas. Penelitian ini merupakan studi kualitatif dengan metode analisis literatur yang bertujuan untuk mengidentifikasi strategi pembelajaran seni berbasis teknologi digital yang adaptif. Data diperoleh dari buku, artikel jurnal, dan publikasi daring yang relevan, menggunakan kata kunci terfokus dalam proses pencarian. Analisis dilakukan melalui pendekatan analisis isi tematik untuk mengelompokkan pola dan isu utama, seperti model blended learning, integrasi STEAM, kesenjangan digital, dan kesiapan guru. Hasil studi menunjukkan bahwa integrasi teknologi dalam pendidikan seni tidak hanya memperkaya proses kreatif, tetapi juga mendukung pengembangan berpikir kritis dan inovasi. Oleh karena itu, diperlukan kurikulum seni rupa yang menggabungkan keterampilan manual tradisional dengan pendekatan digital kontemporer untuk membentuk sistem pendidikan yang inklusif, progresif, dan relevan secara global.